2019
DOI: 10.5530/ptb.2019.5.17
|View full text |Cite
|
Sign up to set email alerts
|

Basic Knowledge of Non-steroidal Anti-inflammatory Drugs among Saudi Community

Abstract: Objectives: The use of non-steroidal anti-inflammatory drugs (NSAIDs) is a rising problem in the modern medical world. NSAIDs are easily available over the counter and accessible to the public. As such, we have seen a need to assess the knowledge and perception of public use of NSAIDs. In this study, we aimed to explore the knowledge of public use of NSAIDs among the participants from major metropolitan areas in the Kingdom of Saudi Arabia. Methodology: This is a cross-sectional study conducted for a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“… 2 , 13 , 18 - 22 A study conducted in Jeddah, Saudi Arabia among NSAIDs users found that approximately 75% of them were not counselled by a healthcare provider on the risks of NSAIDs and more than 90% of them were united in the opinion that greater efforts are needed from healthcare providers in presenting information regarding ADRs. 2 , 13 , 18 - 21 Receiving information about NSAIDs in any way other than from the authorized person may lead to inaccurate and nonspecific information. In addition, the material in the medication leaflets is not suitable for the public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 13 , 18 - 22 A study conducted in Jeddah, Saudi Arabia among NSAIDs users found that approximately 75% of them were not counselled by a healthcare provider on the risks of NSAIDs and more than 90% of them were united in the opinion that greater efforts are needed from healthcare providers in presenting information regarding ADRs. 2 , 13 , 18 - 21 Receiving information about NSAIDs in any way other than from the authorized person may lead to inaccurate and nonspecific information. In addition, the material in the medication leaflets is not suitable for the public.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed inadequate patient knowledge about side effects which require more advice and consultation regarding appropriate management or prevention tips to mitigate the risks of NSAIDs. 2,13,[18][19][20][21][22] A study conducted in Jeddah, Saudi Arabia among NSAIDs users found that approximately 75% of them were not counselled by a healthcare provider on the risks of NSAIDs and more than 90% of them were united in the opinion that greater efforts are needed from healthcare providers in presenting information regarding ADRs. 2,13,[18][19][20][21] Receiving information about NSAIDs in any way other than from the authorized person may lead to inaccurate and nonspecific information.…”
Section: Methodsmentioning
confidence: 99%